Efektivitas Pendekatan PMRI dengan Konteks Nasi Tumpeng pada Materi Volume Kerucut di Kelas IX - Fentika Rahmadona; Helni Indrayati; Indah Widyaningrum (ARITHMETIC: Academic Journal of Math, 2019)
The purpose of this study was to determine the effectiveness of the PMRI approach with the context of cone rice on cone volume material on student learning outcomes in class IX of SMP Negeri 1 Pagaralam 2018/2019 academic year. The method used in this study was True-Experimental Design with a pre-test design posttest control group design. Sample of students including 30 students in the experimental class (IXH) and 32 control class students (IXI). The data collection techniques used were test and documentation. To measure student mathematics learning outcomes in this study used a written test in the form of essays totaling five questions. The hypothesis of the research is PMRI's approach to the context of cone rice in cone volume material is effective on student learning outcomes in class IX of SMP Negeri 1 Pagaralam 2018/2019 academic year. The results of students' mathematics test data using the PMRI approach with the context of cone rice on cone volume material on student learning outcomes in class IX of SMP Negeri 1 Pagaralam in the 2018/2019 academic year were obtained from the average.